Uma proposta de estudo da autonomia docente de professores de ciências e de matemática em exercício - Maciel Junior, Percy Fernandes (2017)
The present work has the objective of analyzing the possibilities of studying the autonomy of teachers in a group of teachers of Science and Mathematics, from their experiences in an educational robotics course, from the perspective of Contreras and Habermas. Such an approach seeks, without diminishing the importance of contents, to withdraw its centrality from the teaching / learning process, bringing the development of the communicative skills of the teacher and his apprentice to the stage of this process. The work is based on the study of teaching autonomy made by the Spanish teacher José Contreras, and the communicative aspects of the course and its subsequent analysis, the German theory model of the argument presented by the philosopher Jürgen Habermas in his work Theory of Communicative Action (TAC). The methodology describes in detail the activities developed along the course as well as the difficulties encountered for its execution, which end up influencing the reflection made by the teachers during the realization of the focus group, who provided us with the material with which we proceed to a content analysis based on the work of French researcher Laurence Bardin. The results point to a limiting effect in the construction of teachers' conception of teacher autonomy provoked mainly by the centrality that the curricular contents have in the educational processes. As a product of this research, a robotics course in WEB format is presented in which the contents are presented as required, both for the assembly and for the analysis of the proposed experiments.